2009
DOI: 10.1021/cr900340q
|View full text |Cite
|
Sign up to set email alerts
|

Parameters for Evaluation of the Fate, Transport, and Environmental Impacts of Chemical Agents in Marine Environments

Abstract: The second paragraph in this section should be revised as follows:A less polar and deep purple cyclized didemnimide alkaloid 72 (with a trivial name of isogranulatimide) was first isolated from the Brazilian ascidian Didemnum granulatum (Subphylum Urochordata, Class Ascidiacea) in late 1998 by Berlinck et al. 1a Almost at the same time, Fenical's group independently obtained this compound from the Caribbean ascidian Didemnum conchyliatum. 2 Compound 72 is the cyclization product of didemnimide A 67 formed vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…The value of x VX,sat = 2.9 × 10 −3 was computed from the approximate solubility of VX in water of 43 mg/mL. 34 Plugging in all of the required values in eq 13 yields γ VX = 346.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The value of x VX,sat = 2.9 × 10 −3 was computed from the approximate solubility of VX in water of 43 mg/mL. 34 Plugging in all of the required values in eq 13 yields γ VX = 346.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Work on destroying these abandoned chemical weapons is still in progress. The main hazards induced by the abandoned SM include environmental pollution (Bizzigotti et al 2008;Sanderson et al 2010) and potential threat to civilians (Xu et al 2014). As a highly reactive alkylating agent, SM can attack nearly all cell constituents and cause severe damage to the skin, eyes and respiratory system.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, reactor testing uses neat (pure) chemical agent dosed with an excess amount of liquid decontaminant, and reaction products are sampled from the reactor reagent volume. However, due to low solubility and/or slow rates of dissolution of the organic chemical agents (e.g., solubility of HD [distilled mustard agent, bis-(2-chloroethyl) sulfide] in water: 92 g/mL), 5 the agent may not be distributed uniformly within the reactor and may present a heterogeneous solution of agent droplets within the decontamination solution. If the agent droplets do not readily or rapidly dissolve, the decontamination reaction occurs primarily on the surface of the liquid agent droplet, and the decontamination rate is mass transport limited because the dissolution rate is much slower than the decontamination reaction rates.…”
Section: Introductionmentioning
confidence: 99%
“…The results demonstrated that (1) hydrolysis of neat HD is rate-limited by the rate of dissolution of HD into water, 5 and (2) the dilute reactor method can be used to isolate the reactive component of decontamination performance. Decontaminants A, G, H, K, and L demonstrated lower reactivity and included solvents (H and K) and non-oxidative alkaline decontaminants (A, G, L).…”
mentioning
confidence: 99%